Integrating the pathogenesis of spondyloarthritis: gut and joint united?. Issue 2 (March 2015) - De Wilde, Katelijne; Debusschere, Karlijn; Beeckman, Sam; Jacques, Peggy; Elewaut, Dirk
Abstract : Purpose of review: The association between spondyloarthritis (SpA) and inflammatory bowel disease (IBD) is well known. Additionally, about half of SpA patients show microscopic gut inflammation. Substantial progress has been made in understanding the pathogenesis of SpA and IBD, with new therapeutic targets for either of them in clinical development. Recent findings: Microscopic gut inflammation was found in early forms of SpA in about 50% of cases and is associated with age, sex, disease activity and degree of MRI inflammation on sacroiliac joints. Although prospective follow-up data in men and murine animal studies show a parallelism between gut and joint evolution in SpA, therapeutic outcomes are not always the same in SpA and IBD. These differences can be ascribed to differences in not only the cytokine pathways and cells involved in disease, tissue localization and environmental factors but also in pharmacokinetics and biodistribution. Summary: A significant amount of data all point in the direction of arthritis and gut inflammation being pathogenetically closely linked in the SpA concept. However, when it comes to therapeutic effectiveness, the gut and the joints do not always react in the same way. These differences in therapeutic effect could be attributed to the different ways in which cytokine pathways are involved in SpA and IBD.